Does hydropower growth threaten fish security under the pathway of sustainable development? Evidence from European Union economies - Mohd Alsaleh; Abdul-Rahim, Abdul Samad (Sage Publications Inc., 2023)
This research explores the impact of hydropower growth on fish supply in European Union Region nations from 1990 to 2019. Using the panel fully modified ordinary least squares, the outcome exhibits the reduced fish supply with the growth in hydropower production. Also, human population density and growth economics were found to be decreasing fish supply and their habitats. While institutional quality and expenditure were found to be increasing fish species and numbers, the finding implies that fish supply in the European Union Region could efficiently be minimized by boosting the quantity of hydropower production with operational procedures. This can ultimately add more burden on an already degraded natural resource and negative environmental impacts. The predicted outcomes are confirmed by dummy panel ordinary least squares and pooled ordinary least squares thus, thought to be valid. The research advised the European Union nations to develop the efficiency and productivity of hydropower in the energy mix to lessen the carbon dioxide releases. The authorities from these nations should further participate in the sustainability of hydropower industry growth by exploring the probability of the unified river managing structures to resolve conflicting economic, political, and ecological benefits. The government of the said nations can similarly stress the sustainability of the hydropower output to reach energy certainty and conservation of fish resources to achieve food security.